2000
DOI: 10.1023/a:1008977416834
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A needle-like apatite-leucite glass-ceramic was prepared in the SiO2-Al2O3-Na2O-K2O-P2O5-F system. Nucleation and crystallization processes were studied in bulk and powdered samples. The crystallization of leucite follows the mechanism of surface crystallization. After the precipitation of NaCaPO4 crystals and another unknown crystal phase, the formation of needle-like apatite is based on a volume nucleation and crystallization process. The mechanism of the formation of needle-like apatite differs to those of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 1 publication
0
19
0
Order By: Relevance
“…We confirmed that the secondary crystalline phase present in BioS-2P was a sodium-calcium phosphate (NaCaPO 4 ) that was difficult to identify due to its low crystallized volume fraction. This phase was also detected in Bioglass 45S5 as well as in other glass-ceramics after heat treatment at temperatures of approximately 1000°C, and the phase was identified as αor β-rhenanite [24][25][26][27]. The secondary crystalline phase was highly reactive in simulated body fluid and acted as a heterogeneous nuclei for hydroxycarbonate apatite growth at glass-ceramic surfaces, including Biosilicate ® [16,27,28], and it improved the mechanical strength, elastic modulus and fracture toughness without affecting the bioactivity index [14].…”
Section: Discussionmentioning
confidence: 86%
“…We confirmed that the secondary crystalline phase present in BioS-2P was a sodium-calcium phosphate (NaCaPO 4 ) that was difficult to identify due to its low crystallized volume fraction. This phase was also detected in Bioglass 45S5 as well as in other glass-ceramics after heat treatment at temperatures of approximately 1000°C, and the phase was identified as αor β-rhenanite [24][25][26][27]. The secondary crystalline phase was highly reactive in simulated body fluid and acted as a heterogeneous nuclei for hydroxycarbonate apatite growth at glass-ceramic surfaces, including Biosilicate ® [16,27,28], and it improved the mechanical strength, elastic modulus and fracture toughness without affecting the bioactivity index [14].…”
Section: Discussionmentioning
confidence: 86%
“…One phase is thought to be calcium, phosphate and fluoride rich, that subsequently crystallizes to fluorapatite and the other phase is thought to be aluminium and silicon rich, that eventually crystallizes to mullite. Related glasses containing alkali metal that also crystallize to fluorapatite have been studied by Hoeland et al [5][6][7]. These glasses show marked evidence of APS on examination by transmission electron microscopy.…”
Section: Introductionmentioning
confidence: 99%
“…5C). Variations in the morphology and volume fraction of these crystals can be expected to affect the optical, mechanical, and thermal expansion characteristics of these materials 46. In this study (Type-1, Table 2) the heat pressed glass-ceramic material produced consistent E values with low standard deviations illustrating material consistency and the reliability of this testing method.…”
Section: Discussionmentioning
confidence: 55%
“…Höland et al45 suggested these fibres were fluorapatite crystals. The growth of fluorapatite crystals has been reported to follow an Oswald ripening mechanism, where larger crystals grow at the expense of smaller crystals,4647 and this may be responsible for the larger particulates found within the microstructure (Fig. 5C).…”
Section: Discussionmentioning
confidence: 95%